Indicator approach to housing market analysis in Sarawak - Voon, Zhi Cheng (Universiti Malaysia Sarawak, (UNIMAS), 2015)
The present study evaluated the movement of housing cycle in Sarawak. A housing market indicator has been constructed for the case of Sarawak through an indicator methodology founded by The National Bureau of Economics Research (NBER) of the United States. Furthermore, various empirical issues such as stationarity of time series, cointegration of variables, indicator construction and filtering exercise have been examined empirically to administer further understanding towards the construction of indicator. In addition, the objective to construct a novel housing market indicator (HMI) with leading attributes is believed to be successful. The constructed HMI displayed an outstanding leading period of 10 months on average. Moreover, the HMI is found to be moving consistently with the housing price index (HPI) of Sarawak in terms of magnitude and also successfully traced down all the major economic incidents that affected Sarawak. In a nutshell, the HMI has provided a remarkable outlook on the housing market dynamic in Sarawak. The findings of this present study may serve as a good reference of the housing cycle in Sarawak. Policy maker, business sector and household investors can have a better insight towards the fluctuation movement of the housing market and carry out their plans in the investment and policy development in housing sector.